2017
DOI: 10.3390/ijms18081406
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Reparative Mechanisms of Mesenchymal Stem Cells for Retinal Diseases

Abstract: The use of multipotent mesenchymal stem cells (MSCs) has been reported as promising for the treatment of numerous degenerative disorders including the eye. In retinal degenerative diseases, MSCs exhibit the potential to regenerate into retinal neurons and retinal pigmented epithelial cells in both in vitro and in vivo studies. Delivery of MSCs was found to improve retinal morphology and function and delay retinal degeneration. In this review, we revisit the therapeutic role of MSCs in the diseased eye. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 115 publications
(156 reference statements)
0
77
0
1
Order By: Relevance
“…MSCs have shown promising outcomes in preclinical and clinical studies for treating pain and degenerative diseases such as AD, DDD, MS, PD, and RDD and providing immunomodulatory, neuroprotective, and anti‐inflammatory responses in vivo (Beeravolu et al, ; Ding, Kumar, & Mok, ; Gugliandolo, Bramanti, & Mazzon, ; Nasri et al, ; Osborne, Sanderson, & Martin, ; Perez‐Cruet et al, ; Turgeman, ; van Buul et al, ; R. Zhang, Liu, et al, ). Studies have shown that MSCs can be differentiated to NPCs to regenerate the NP in the IVD and to retinal progenitor cells to regenerate the retina within the eye (Beeravolu et al, ; Ding et al, ; Perez‐Cruet et al, ). Furthermore, MSCs have the ability to exert an anti‐inflammatory and immunomodulatory response (R. Zhang, Liu, et al, ).…”
Section: Opportunitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…MSCs have shown promising outcomes in preclinical and clinical studies for treating pain and degenerative diseases such as AD, DDD, MS, PD, and RDD and providing immunomodulatory, neuroprotective, and anti‐inflammatory responses in vivo (Beeravolu et al, ; Ding, Kumar, & Mok, ; Gugliandolo, Bramanti, & Mazzon, ; Nasri et al, ; Osborne, Sanderson, & Martin, ; Perez‐Cruet et al, ; Turgeman, ; van Buul et al, ; R. Zhang, Liu, et al, ). Studies have shown that MSCs can be differentiated to NPCs to regenerate the NP in the IVD and to retinal progenitor cells to regenerate the retina within the eye (Beeravolu et al, ; Ding et al, ; Perez‐Cruet et al, ). Furthermore, MSCs have the ability to exert an anti‐inflammatory and immunomodulatory response (R. Zhang, Liu, et al, ).…”
Section: Opportunitiesmentioning
confidence: 99%
“…MSCs have shown promising outcomes in preclinical and clinical studies for treating pain and degenerative diseases such as AD, DDD, MS, PD, and RDD and providing immunomodulatory, neuroprotective, and anti-inflammatory responses in vivo Ding, Kumar, & Mok, 2017;Gugliandolo, Bramanti, & Mazzon, 2017;Nasri et al, 2018;Osborne, Sanderson, & Martin, 2018;Perez-Cruet et al, 2018;Turgeman, 2015;van Buul et al, 2014;R. Zhang, Liu, et al, 2013).…”
Section: Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Stem cells are undifferentiated cells that have the ability to self-renew and differentiate into mature cells. This target can be reached by delivering embryonic stem cells (ESC), induced pluripotent stem cells (iPSC), or mesenchymal stem cells (MSC) into the eye in specific ways (Idelson et al, 2009;Klassen 2015;Takahashi and Yamanaka 2013;Ding et al, 2017). ESC, iPSC, and MSCs are characterized by self-renewal and multipotency, i.e., the ability to differentiate into the different cells of the three germ layers.…”
Section: Introductionmentioning
confidence: 99%
“…Excess generation of ROS causes damage to membrane lipoproteins and cellular DNA, thus leading to apoptosis and photoreceptor death [66][67][68][69]. The GFs excreted by grafted mesenchymal cells can facilitate Bcl-2 gene expression in order to avoid the unrelenting cell death [21]. Bcl-2 family proteins are most notable for their regulation of apoptosis by interacting with caspases [70][71][72][73][74][75].…”
Section: Discussionmentioning
confidence: 99%